2023
DOI: 10.3390/bs13020136
|View full text |Cite
|
Sign up to set email alerts
|

Growing in Adversity: A Narrative Study of Resilience Generation in Chinese Families of Children with ASD

Abstract: Referring to Walsh’s theoretical framework of family resilience while taking into account China’s own cultural and institutional context, this study discussed the process of resilience generation in Chinese families of children with ASD. A qualitative approach was taken, using narrative research on 10 Chinese families of children with ASD. Category-content analysis of the data suggests that the generation of resilience in Chinese families of children with ASD is influenced by four factors: (A) cultivating posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In line with the previous studies [39,40], the traditional Chinese parenting approach, characterized by its authoritarian nature, remains prevalent among parents. This authoritarian style emphasizes discipline as a primary means of addressing children's behavioral challenges, often using tactics such as behavioral reinforcement and, at times, punishment [74].…”
Section: Adjusting Parenting Stylessupporting
confidence: 72%
See 2 more Smart Citations
“…In line with the previous studies [39,40], the traditional Chinese parenting approach, characterized by its authoritarian nature, remains prevalent among parents. This authoritarian style emphasizes discipline as a primary means of addressing children's behavioral challenges, often using tactics such as behavioral reinforcement and, at times, punishment [74].…”
Section: Adjusting Parenting Stylessupporting
confidence: 72%
“…Within a collectivist culture that places a high value on social responsibilities, personal obligations, and family unity, familial ties often grow stronger. Grandparents often contribute significantly to daily parenting activities [39], and parents demonstrate remarkable self-sacrifice by altering their personal lives for the well-being of their children [32,40,41].…”
Section: Culture-related Coping Experiences Among Chinese Parents Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A narrative study conducted in China explored resilience in families of children with ASD and found that cultivating positive family beliefs, adjusting the family's organizational pattern, actively expanding external resources, and optimizing family communication enhanced family resilience and coping with adversity (Gao et al, 2023). Acceptance of the diagnosis was identified as a crucial step for families to develop resilience and adapt to the changes they face together (Frye, 2016).…”
Section: Resiliencementioning
confidence: 99%